Identification of Economic Potential and Human Resources in the Transmigration Area of Bombana Regency, Southeast Sulawesi Province - Asymar, Hasta Herlan; Erri, Dirgahayu; Muhammad, Agit; Uthami, I Gusti Ayu Agung Dewi Kurnia (ProBisnis : Jurnal Manajemen, 2023)
The essence of implementing transmigration is to achieve prosperity, equitable development, and to act as a glue for national unity. In this identification study, 4 (four) criteria were selected to assess regional spatial potential for the development of Transmigration Areas, namely (1) Criteria for land availability and carrying capacity, (2) Criteria for local economic development, (3) Criteria for population development, and (4) Criteria for local economic development. ) Criteria for supporting transmigration policies and programs. The results of the identification of potential Transmigration areas in Bombana Regency, which culminated in the delineation of regional spaces which are expected to be developed into future Transmigration Areas, are input for the Regional Government (Regency and/or Province) regarding their regional development and development efforts. Development of Transmigration Areas can be one of the development program options to encourage or realize the growth/development of parts of the district that are relatively undeveloped, and lagging behind compared to parts of the district that are already developed and developing. Transmigration development is cross-sectoral so a common understanding is needed between all regional stakeholders so that each party can contribute according to their main tasks and functions